Vì \(-2\le a;b;c\le5\Rightarrow\hept{\begin{cases}\left(a+2\right)\left(a-5\right)\le0\\2\left(b+2\right)\left(b-5\right)\le0\\3\left(c+2\right)\left(c-5\right)\le0\end{cases}}\) \(\Leftrightarrow\hept{\begin{cases}a^2-3a-10\le0\\2b^2-6b-20\le0\\3c^2-9b-30\le0\end{cases}}\)
\(\Rightarrow a^2+2b^2+3c^2-3\left(a+2b+3c\right)-60\le0\)
\(\Rightarrow a^2+2b^2+3c^2\le3\left(a+2b+3c\right)+60\le3.2+60=66\) (ĐPCM)
Dấu "=" xảy ra \(\Leftrightarrow\orbr{\begin{cases}a=-2\\a=5\end{cases};\orbr{\begin{cases}b=-2\\b=5\end{cases};\orbr{\begin{cases}c=-2\\c=5\end{cases}}}}\)